(untitled) (Central Asian Journal of Medical Sciences, 2020)
Objectives: This study was conducted to determine the effect of Hepatitis B infection with or without D coinfection on the hepatitis flare associated with chemotherapy for B-Cell non-Hodgkin lymphoma. Methods: The hepatitis flare related to the chemotherapy for newly diagnosed B-Cell non-Hodgkin lymphoma was studied in HBV mono-infected and HBV and HDV coinfected patients between 2015 and 2018. Results: Nineteen HBsAg positive patients satisfied the inclusion criteria. In the group with the hepatitis flare, 14.3% were anti-HDV negative and 83.3% were anti-HDV positive (p<.006). Also, the hepatitis flare occurred in all patients where HDV-RNA was detected, while it had occurred in 60% of patients where HDV-RNA was not detected. Conclusion: The hepatitis flare related to chemotherapy occurred more frequently in B-Cell non-Hodgkin lymphoma patients coinfected with HBV and HDV without antiviral prophylaxis, especially when HDV-RNA was detected.